Antioxidant and Anti-Inflammatory Properties of Anacardium occidentale Leaf Extract. (17th August 2017) - Souza, Natália Cabral; de Oliveira, Juliana Medeiros; Morrone, Maurílio da Silva; Albanus, Ricardo D'Oliveira; Amarante, Maria do Socorro Medeiros; Camillo, Christina da Silva; Langassner, Silvana Maria Zucolotto; Gelain, Daniel Pens; Moreira, José Cláudio Fonseca; Dalmolin, Rodrigo Juliani Siqueira; Pasquali, Matheus Augusto de Bittencourt
Abstract : In tropical America, principally in Northeastern Brazil, the leaf extract of Anacardium occidentale is traditionally used for treatment of different diseases. However, chemical and biological properties and activities of Anacardium occidentale are poorly investigated and known. Here, we evaluated the antioxidant and anti-inflammatory activities "in vitro" of leaf extract from Anacardium occidentale. Our results show that leaf extract exhibits antioxidant activity when used to treat RAW 264.7 macrophage cells. Antioxidant effects were observed by decrease in oxidative damage in macrophage cells treated with 0.5 µ g/mL and 5 µ g/mL of leaf extract. Moreover, leaf extract reversed oxidative damage and inflammatory parameters induced in LPS-stimulated RAW 264.7 macrophage cells. Leaf extract at 0.5 µ g/mL and 5 µ g/mL was able to inhibit release of TNF- α and IL-1 β in LPS-stimulated cells. Taken together, our results indicate antioxidant and anti-inflammatory effects of leaf extract from Anacardium occidentale and reveal the positive effects that intake of these products can mediate in biological system.